Predicting Mortality in Patients With "Malignant" Middle Cerebral Artery Infarction Using Susceptibility-Weighted Magnetic Resonance Imaging: Preliminary Findings. Issue 8 (February 2016) - Chao, Shu-Ping; Chen, Chia-Yuen; Tsai, Fong Y.; Chan, Wing P.; Chen, Chin-I
Abstract : Abstract: To evaluate malignant middle cerebral artery (MCA) infarction (defined as space-occupying edema in more than 50% to 75% of the MCA territory) on magnetic resonance imaging (MRI) with susceptibility-weighted imaging (SWI) sequence and assess the usefulness of SWI findings, diffusion-weighted imaging (DWI) findings, and apparent diffusion coefficient (ADC) as predictors of clinical outcome. Data from 16 patients with large MCA infarction previously admitted to our institution between December 2009 and October 2012 were retrospectively collected and analyzed. Within 7 days after stroke onset, 1 neurologist and 1 neuroradiologist estimated the area of infarction on DWI/ADC and extent of prominent vessel sign (PVS) on SWI images using the Stroke Program Early MR Score (SPEMRS). The PVS on SWI was defined as a local prominence of hypointense vessels with either increased vessel number or diameter in the target area, when compared with the number or diameter of the contralateral MCA territory vessels. Six patients died and 10 survived. Although the DWI/ADC-SPEMRS and clinical profiles were similar between the nonsurvivor and survivor groups, SWI-SPEMRS was significantly lower in the nonsurvivor group ( P  < 0.001). The area of deoxygenation on SWI in patients with malignant MCA infarction can predict mortality. Lower SWI-SPEMRS is a potentially better predictor of poor outcome than lower DWI-SPEMRS. A larger prospective study is needed to clarify the role of SWI as a therapeutic guide in malignant MCA.